Karakteristik Reproduksi dan Perkembangan Populasi Kambing Peranakan Etawah di Lahan Pasca Galian Pasir - Kurniasih, N. N.; Fuah, A. M.; Priyanto, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
The Grade Goats of Etawah and local goats which commonly called,”Etawah Grade Goats” is well adapted to the enviromental of Indonesia. These animals are also well maintained and kept by farmers as the main producers of meat and milk. The aim of this research was to study the reproductive characteristics and population dynamics of Etawah grade goats in Sumedang of West Java. This research was conducted from July to August of 2011 in Cimalaka and Paseh subdistricts of Sumedang. Thirty six (36) farmers were purposively chosen as respondents for this study. Primary data were obtained from the farmers by interview using questionnaires. Secondary data were collected from Sumedang livestock office and statisticaly reported from farmers group. Data were analyzed descriptively to obtain reproductive characteristics of Etawah gradegoats. Based on the reproductive characteristics obtained, an estimation was made on the population dynamics of dairy goats in Cimalaka and Paseh subdistricts. The average age of ewes at first estrus was 10.06±1.65 m and 12.89±3.86 m in Cimalaka and Paseh respectively. The first conception of ewes occurred at 10.56±1.55 m and 13.26±3.93 m, and kidding interval was 7.75±0.58 m and 7.17±1.11 m whereas, the mortality rate of young goats was 8% and 24% in Cimalaka and Paseh respectively which was varied between region. The results of estimation made from population dynamics of dairy goats in the Cimalaka subdistricts indicated that the increase rate of goats after six years was 11.43%,The increasing of goat numbers obtained six years, to be 308 heads. Therefore, the number of ewes should be kept in the flock was 79 heads in orderto maintain population.The results of estimation made from population dynamics of dairy goats in the Paseh subdistricts indicated that the decrease on rate of goats after six years was 23.37%, that resulted in the decreasing of goat numbers obtain six years to be 41 heads. Therefore the number of ewes should be kept in the flock was 8 heads in order to maintain population.